Пусть tgx=t
тогда
t^2+5t+6=0
D=52–4·6=25–24=1
t=(–5–1)/2=–3 или t=(–5+1)/2=–2
подставляем обратно и решаем
tgx = – 3 ⇒ x= arctg(–3)+πk, k ∈Z
⇒ x=–arctg3+πk, k ∈ Z
или
tgx = – 2 ⇒ x= arctg(–2)+πn, n ∈Z
⇒ x=–arctg2+πn, n ∈ Z
Пошаговое объяснение:
(tgx)^2-5tgx+6=0
Пусть tgx=t (при этом t≠π\2+πn, n∈Z), тогда:
t^2-5t+6=0
D=25-4*6=1^2
t1=(5+1)\2=3
t2=(5-1)\2=2
Обратная замена:
tgx=3 > x=arctg3+πn, n∈Z
tgx=2 > x=arctg2+πn, n∈Z
Пусть tgx=t
тогда
t^2+5t+6=0
D=52–4·6=25–24=1
t=(–5–1)/2=–3 или t=(–5+1)/2=–2
подставляем обратно и решаем
tgx = – 3 ⇒ x= arctg(–3)+πk, k ∈Z
⇒ x=–arctg3+πk, k ∈ Z
или
tgx = – 2 ⇒ x= arctg(–2)+πn, n ∈Z
⇒ x=–arctg2+πn, n ∈ Z
Пошаговое объяснение:
(tgx)^2-5tgx+6=0
Пусть tgx=t (при этом t≠π\2+πn, n∈Z), тогда:
t^2-5t+6=0
D=25-4*6=1^2
t1=(5+1)\2=3
t2=(5-1)\2=2
Обратная замена:
tgx=3 > x=arctg3+πn, n∈Z
tgx=2 > x=arctg2+πn, n∈Z